Study on Pore Structure of Tectonically Deformed Coals by Carbon Dioxide Adsorption and Nitrogen Adsorption Methods - Jinbo Zhang; Huazhou Huang; Wenbing Zhou; Lin Sun; Zaixing Huang (Energies)
The study of pore characteristics in tectonic coal is essential for a deeper understanding of gas diffusion, seepage, and other transport processes within coal seams, and plays a crucial role in the development of coalbed methane resources. Based on low-temperature N2 and CO2 adsorption experiments, this study investigated the pore structure characteristics of four tectonic coal samples collected from the Hegang and Jixi basins in China. The results show that the mylonitic coal sample exhibits a clear capillary condensation and evaporation phenomenon around a relative pressure (P/P0) of 0.5. The degree of tectonic deformation in coal has a significant impact on its pore characteristics. As the degree of deformation increases, both the pore volume and specific surface area of the coal gradually increase. The pore volume and specific surface area of micropores are primarily concentrated in pores with diameters of 0.5–0.7 nm and 0.8–0.9 nm, while those of mesopores are mainly distributed in pores with diameters of 2.3–6.2 nm. The proportion of pore volume and specific surface area contributed by micropores is much greater than that of mesopores. The fractal dimension is positively correlated with the degree of tectonic deformation in coal. As the fractal dimension increases, the average pore diameter decreases, closely tied to the destruction and reconstruction of the coal’s pore structure under tectonic stress. These findings will contribute to a deeper understanding of the pore structure characteristics of tectonic coal and effectively advance coalbed methane development.